Combined of Thermionic Convertor and Brayton Cycle - H. A. Swissi , M. A. Alabdoadaim (Journal of Pure & Applied Sciences, 2019)
The increasing demand for electric power doubled the efforts of specialists to search for efficient power systems, and as a result of composite thermal systems, which relied on the investment of thermal energy released from the process of combustion to the maximum extent, which increased the electrical capacity produced and improved thermal efficiency, the continued development of the field of thermal systems Connecting a direct conversion system such as Thermionic Energy Convertors thermal ionizer to a conventional one such Brayton Cycle as a simple gas cycle forms a new composite thermal system with a large productive capacity by investing in thermal energy.The release of the single combustion process in a simple gas cycle to the maximum extent possible, which maintained a limited stock of fossil energy, and helped to reduce the amount of exhaust gases emitted into the atmosphere. A basic model of the composite thermal system was formed where the emitter is fed Thermionic Energy Convertors by part of the combustion products from the simple gas cycle fuel combustion process, and the collector cooled by the Thermionic Energy Convertors with part of the exhaust gases from the gas turbine emitted into the air. Also, a modified model was designed for the basic model of the proposed thermal system, the modified model has the same components as the basic model, and the process of feeding the emitter with the modified model is done in the same way as the basic model, the difference between the two models lies in the mechanism of cooling the pool, the results obtained indicate the performance of the basic model of the thermal system The proposed vehicle of the modified model when raising the pressure ratio simple gas cycle achieved the highest thermal efficiency when selecting the basic model and operating at high pressure ratios where the thermal efficiency(42.5%),the best value of the total power obtained when Gail modified model with low pressure ratios.